AB0201 Altered Serum Fatty Acid Profiles in Patients with Polymyositis or Dermatomyositis Compared to Healthy Individuals and in Relation to Immunosuppressive Treatment. (9th June 2015) - Raouf, J.; Idborg, H.; Olsson, P.; Jakobsson, P.-J.; Lundberg, I.E.; Korotkova, M.
Abstract : Background: Polymyositis (PM) and dermatomyositis (DM) are chronic autoimmune diseases, characterized by muscle fatigue and low muscle endurance. Histopathological characteristics of muscle biopsies are infiltration of inflammatory cells, muscle fiber degeneration and regeneration. Conventional treatment includes high doses of glucocorticoids and immunosuppressive drugs, however, only a limited number of patients recover muscle function. Our group has recently found that immunosuppressive treatment has significant effects on gene expression related to lipid and fatty acid (FA) metabolism that may contribute to the persistent muscle weakness often seen in myositis patients. Lipid dysregulation might lead to generation of lipotoxic mediators which contribute to cell dysfunction or death. Furthermore, a number of studies have confirmed the important effects of FA on skeletal muscle growth, strength and inflammation. However the involvement of lipids and FA in the pathogenesis of polymyositis and dermatomyositis has not been clarified. Objectives: To analyze lipid and FA profiles in sera from patients with polymyositis or dermatomyositis in comparison to healthy individuals and in relation to immunosuppressive treatment. Methods: Serum samples were obtained from 14 patients with established PM or DM and 12 healthy individuals. Serum lipids were extracted by using liquid-liquid extraction (LLE). FA composition of total lipids was determined by gas chromatography flame ionization detector (GC-FID). FA composition of several lipid classes e.g., triacylglycerols, phospholipids, sphingolipids and lysophospholipids was analyzed by using liquid chromatography tandem mass spectrometry (LC-MS/MS). In addition, serum samples from 8 myositis patients before and after 6 months of immunosuppressive treatment was extracted by LLE and analyzed by LC-MS/MS. Results: Our preliminary results suggest that FA composition of total serum lipids was different in myositis patients compared to healthy donors; the levels of palmitic16:0 acid was significantly higher (<0.05) in myositis patients whereas the levels of arachidonic 20:4 (n-6) acid was significantly lower (p=0.05). Immunosuppressive treatment did not affect the total levels of lipid classes in the serum from myositis patients. However, the levels of phosphatidylcholine (PC) PC (32:1), phosphatidylethanolamine (PE) PE (36:5) and lysophosphatidylcholine (LPC) LPC (16:1) were all significantly higher (p<0.05) in myositis patients after 6 months of immunosuppressive treatment. Conclusions: FA composition of total serum lipids is altered in myositis patients compared to healthy controls. Immunosuppressive treatment resulted in changed FA composition of serum PC, PE and LPC. These findings indicate that FA metabolism might be deregulated in PM and DM patients and may be further affected by immunosuppressive treatment. Disclosure of Interest: None declared